Virtual Reality in Space Technology Education - Ghada Atta; Amal Abdelsattar; Dalia Elfiky; Mohamed Zahran; Mohamed Farag; Salwa O. Slim (MDPI AG, 2022)
The simplification of space science and technology for students K-12 is a challenging task for educators. Virtual reality and augmented reality are educational techniques that introduce the concept of educational games. Moreover, those techniques have a stunning effect on students. This work presents the utilization of virtual reality models to teach students about the satellite types, satellite subsystems, the satellite assembly and integration process, watching the rocket launch carrying the satellite and observing the satellite in its orbit in virtual space laboratories. A 10-min mission in virtual laboratories will effectively improve the learning outcomes. In addition to the VR feature, a set of activities and short movies are considered to be beneficial for use by students to enrich the teaching results. Finally, the VR model results confirmed that the students' knowledge about the space technology cycle is boosted.